Instead of a Novel: Sophia Yablonska's Travelogues in the History of Modern Ukrainian Literature. Issue 1 (1st March 2020) - Haleta, Olena
Abstract: This article focuses on the life and literary strategies of Sophia Yablonska (1907–1971), a self-identified Ukrainian camerawoman, photographer, and writer. While working for a French documentary production company, traveling around the world, and living in Morocco and China, Yablonska published three books of travelogues supported by hundreds of photos ( The Charm of Morocco, 1932; From the Country of Rice and Opium, 1936; and Distant Horizons, 1939) that combine autobiographical and anthropological approaches and transgress poetic and narrative conventions. In her travelogues, Yablonska examines the contradictions between traditional and modern culture and expresses them in verbal and visual forms. Abandoning the genre of the novel for that of the travelogue, Sophia Yablonska transgressed literary and life norms in terms of genre, gender, anthropology, autobiography, perception, media, culture, and discourse. Her writings not only reveal other countries, but also show the formation of a modern personality in the process of writing.